The popularity of political persuasive messages among beginner voters about the 2024 election content on social media posts - Gushevinalti Gushevinalti; Nurul Renaningtias (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
This study aims to map what social media is popular among beginner voters as a political reference for the 2024 election. Furthermore, this study will examine persuasive political messages that appeal to novice voters so that it will illustrate what message formulas are popular among novice voters. This research will use a qualitative approach with data collection methods through open questionnaires to explore informants' social media use habits, mandala interviews, and Focus Group Discussions. Informants will be selected using purposive sampling techniques, namely first-time voters who have not been used to vote in regional elections, aged 17-18 years in 2023, and who actively access political information on social media. The results of the menu research show that the message formula that gets the attention of novice voters is in a way that is not pushy or persuasive. Use slang that is easy to understand and not rigid (implicitly does not contain the candidate's vision, mission, and program). Message packaging in videos and photos is more beautiful to novice voters than text because it aligns with social media, which is generally interested in Instagram and TikTok.